2001
DOI: 10.1021/ja010756d
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Cyclic ADP-carbocyclic-ribose, a Stable Mimic of Ca2+-Mobilizing Second Messenger Cyclic ADP-Ribose1

Abstract: The synthesis of cyclic ADP-carbocyclic-ribose (cADPcR, 4) designed as a stable mimic of cyclic ADP-ribose (cADPR, 1), a Ca2+-mobilizing second messenger, was achieved using as the key step a condensation reaction with the phenylthiophosphate-type substrate 14 to form an intramolecular pyrophosphate linkage. The N-1-carbocyclic-ribosyladenosine derivative 16 was prepared via the condensation between the imidazole nucleoside derivative 17, prepared from AICA-riboside (19), and the readily available optically ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 31 publications
2
92
0
Order By: Relevance
“…Later, Lee et al [5] solved the structure of cADPR by x-ray crystallography and showed that it is a novel cyclic nucleotide formed by the covalent linkage of the N1 nitrogen of the adenine ring to the anomeric carbon of the terminal ribose to become a closed cyclic structure (Figure 2). Benefiting from the identified structure, multiple cADPR analogs have been synthesized, which greatly promoted research on the role and mechanism of cADPR-mediated Ca 2+ signaling [6][7][8][9] . From the very beginning of research on cADPR, several pharmacological studies have clearly shown that the mechanism of cADPR-induced Ca 2+ release is different from that of IP3.…”
Section: The Structure and Function Of Cadprmentioning
confidence: 99%
“…Later, Lee et al [5] solved the structure of cADPR by x-ray crystallography and showed that it is a novel cyclic nucleotide formed by the covalent linkage of the N1 nitrogen of the adenine ring to the anomeric carbon of the terminal ribose to become a closed cyclic structure (Figure 2). Benefiting from the identified structure, multiple cADPR analogs have been synthesized, which greatly promoted research on the role and mechanism of cADPR-mediated Ca 2+ signaling [6][7][8][9] . From the very beginning of research on cADPR, several pharmacological studies have clearly shown that the mechanism of cADPR-induced Ca 2+ release is different from that of IP3.…”
Section: The Structure and Function Of Cadprmentioning
confidence: 99%
“…However, new enzyme-independent methods Shuto et al, 2001) should allow for more analogs with structural diversity.…”
Section: 5-di-(tert-butyl)-14-benzohydroquinonementioning
confidence: 99%
“…3-Deaza-cADPR differs from cADPR by the substitution of carbon for nitrogen at the purine ring 3-position (Wong et al, 1999). In cADPcR, the oxygen atom in the cADPR N-1-ribose ring is substituted by a methylene group (Fukuoka et al, 1999;Shuto et al, 2001). 2Ј A -DeoxycADPR has a deletion of the cADPR 2Ј-position hydroxyl group of the ribose moiety linked to the adenine, i.e., the adenosine ribose .…”
Section: 5-di-(tert-butyl)-14-benzohydroquinonementioning
confidence: 99%
“…Acidic deprotection of 16 finally furnished cADPcR (2). 32) cADPcR was not only both chemically and biologically stable, but also effectively mobilizes intracellular Ca 2+ in sea urchin eggs 32) and is more potent than cADPR in neuronal cells. 33) In addition, cADPcR induced insulin secretion from digitonin-permeabilized rat islets via Ca 2+ -mobilization like as cADPR.…”
Section: Cadpcr As a Stable Analogue Of Cadprmentioning
confidence: 96%